Successful treatment of severe Reiter's syndrome associated with human immunodeficiency virus infection with etretinate. Report of 2 cases - Louthrenoo W. (2014)
Two patients who presented with severe Reiter's syndrome were found to have human immunodeficiency virus (HIV) infection. Their arthritis and cutaneous lesions responded poorly to nonsteroidal antiinflammatory drugs and topical corticosteroid therapy. Dramatic improvement of the arthritis and cutaneous lesions was seen 4 weeks after etretinate was added to the treatment. The potential role of etretinate in the treatment of severe Reiter's syndrome associated with HIV infection is emphasized.